A reactive asphalt cold patch material and preparation method thereof
By optimizing the material formula and preparation process of reactive asphalt cold feed, combined with photocuring technology, the problems of insufficient permeability and slow reaction speed of existing leakage treatment materials have been solved, and efficient, environmentally friendly and low-cost leakage treatment effect has been achieved.
Patent Information
- Application Number
- CN202510033030.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing leak treatment materials have problems such as insufficient permeability, slow reaction speed, complex material ratio, high cost, poor environmental adaptability, insufficient environmental protection, insufficient long-term stability and durability, and high construction process requirements.
By optimizing the material formulation and preparation process, a highly permeable grouting material is provided, whose composition includes aggregates, mineral powder, fillers, diffusion oil and asphalt cold liquid rehydration. It uses photocuring technology to quickly cure, simplify material proportions, reduce costs, improve environmental adaptability and environmental protection, and improve long-term stability and durability.
It improves the permeability and reaction speed of the material, simplifies the material ratio, reduces construction costs and environmental pollution, improves the long-term stability and durability of the material, and simplifies the construction process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy-saving and environmentally friendly building materials, and in particular relates to a reactive asphalt cold patch material and a preparation method thereof. Background Art
[0002] Reactive asphalt cold patch is a new type of road repair material, mainly used to quickly repair defects such as potholes on asphalt pavements. With the rapid development of the transportation industry, the demand for road maintenance and repair is increasing. However, there are many problems with traditional hot-mix asphalt mixtures during construction: hot-mix asphalt requires high-temperature heating, and construction is greatly affected by ambient temperature. The hot-mix process requires a lot of energy, which increases costs and produces a lot of greenhouse gas emissions. The construction process is complicated and time-consuming, which can easily cause traffic congestion. Traditional cold patch materials have low early strength and poor durability, and it is difficult to meet the needs of efficient and long-term repairs.
[0003] To overcome the above problems, cold patch technology has gradually become a research hotspot. Cold patch asphalt mixture does not need to be heated and can be constructed at room temperature. It is energy-saving, environmentally friendly and convenient to construct. According to different material compositions and curing methods, cold patch materials can be divided into emulsified, solvent-based and reactive types.
[0004] Reactive cold patch material is made by mixing high molecular polymers such as resin with curing agent and aggregate at room temperature, and improving the material strength through chemical cross-linking reaction. Its main features include: fast curing speed, which can be opened to traffic in a short time. It has excellent high temperature stability, low temperature crack resistance and water stability. No heating is required, which reduces energy consumption and carbon emissions. It is suitable for a variety of environmental conditions and does not require complex equipment.
[0005] In recent years, light-curing technology has been introduced into reactive asphalt cold patch materials, which can rapidly cure the material by initiating polymerization reactions with ultraviolet or visible light. This technology further improves the performance of cold patch materials: the photoinitiator initiates the polymerization reaction and forms an active chain with the dispersant, thereby activating the curing agent to produce free radicals, which combine with the unsaturated double bonds in the resin to complete the curing. The light-curing process not only improves the early strength of the material, but also significantly shortens the curing time.
[0006] European countries began to study emulsified asphalt cold patch materials as early as the beginning of the 20th century. For example, France developed emulsified asphalt with controllable demulsification time, and the United States issued the "Cold Paving Asphalt Mixture Manual", which provided technical standards for engineering applications. Japan studied epoxy modified asphalt and improved the mechanical properties of the material through epoxy resin, but its high cost limited its application. my country began to study cold patch materials in the 1970s, and currently mainly focuses on mixture proportion design, performance evaluation and other aspects. For example, Sichuan Highway Science and Technology Company has developed cold patch materials suitable for different highway grades, which significantly improved the material adhesion and strength.
[0007] Although reactive asphalt cold patch material has many advantages, it still has some shortcomings: the relatively high cost limits its large-scale promotion.
[0008] It has high requirements on raw materials and processes, and the formula design needs to be further optimized to reduce costs and improve performance.
[0009] Storage stability and construction convenience need to be further improved to adapt to a wider range of application scenarios.
[0010] In summary, reactive asphalt cold patch material and its preparation method are important innovations in the field of road repair. After combining with light-curing technology, it shows better performance and is expected to become an important material for future green transportation construction. However, the process and formula still need to be further optimized to achieve a wider range of engineering applications. Summary of the invention
[0011] Problem to be solved
[0012] The present invention aims to solve the following problems existing in the practical application of existing water leakage treatment materials: Insufficient permeability: Traditional grouting materials such as cement-based slurry, water glass slurry, etc. have high viscosity and are difficult to penetrate into small cracks and pores, resulting in poor water blocking effect.
[0013] Slow reaction speed: The cement-based slurry takes a long time to solidify, which affects the construction efficiency and increases the construction cost and time.
[0014] Complex material ratio: The ratio of existing materials needs to be precisely controlled. Any carelessness may lead to a decrease in material performance and great difficulty in construction.
[0015] High cost: High-performance materials such as polyurethane and acrylates are relatively expensive, which increases the economic burden of the project.
[0016] Poor environmental adaptability: The performance of some materials is unstable in low or high temperature environments, which affects the construction effect and durability of the materials.
[0017] Insufficient environmental protection: Some chemical grouting materials may release harmful substances during the curing process, affecting groundwater resources and the environment.
[0018] Insufficient long-term stability and durability: The solidified material is not strong enough and can be easily washed away under high water pressure, resulting in a short-lasting water blocking effect.
[0019] The construction process has high requirements: it requires a professional construction team and equipment, the construction is difficult, and the complexity of the construction is increased.
[0020] The present invention provides a high permeability grouting material for water leakage control and a preparation method thereof by optimizing the material formula and preparation process, so as to solve the above problems and improve the construction efficiency and quality of underground engineering. Specifically, the present invention aims to: improve permeability: ensure that the slurry can penetrate into small cracks and pores to form a continuous consolidation body.
[0021] Accelerate the reaction speed: It can solidify quickly during the construction process and reduce the construction time.
[0022] Simplify material ratio: By optimizing the formula, reduce the complexity of the ratio and reduce the difficulty of construction.
[0023] Reduce costs: Use low-cost raw materials to reduce the economic burden of the project.
[0024] Enhance environmental adaptability: The material can adapt to different geological conditions and temperature changes, improving the construction effect and durability of the material.
[0025] Improve environmental protection: The material is non-toxic and harmless, meets environmental protection requirements, and reduces pollution to groundwater resources and the environment.
[0026] Improve long-term stability and durability: The cured material has sufficient compressive and tensile strength to ensure long-term water blocking effect.
[0027] Simplify the construction process: By optimizing the preparation method, the construction difficulty can be reduced and the dependence on professional equipment and teams can be reduced.
[0028] Technical Solution
[0029] To solve the above problems, the present invention adopts the following technical solutions.
[0030] A reactive asphalt cold patch material, the components of which are as follows, measured in parts by weight: 90-94 parts of aggregate; 1-3 parts of mineral powder; 0.2-0.7 parts of filler; 0.5-3.0 parts of diffusion oil; and 4-8 parts of asphalt cold patch liquid.
[0031] The asphalt cold patching liquid is composed of the following components in parts by weight: 60-88 parts of base asphalt; 12-38 parts of unsaturated polyester resin; 0.05-0.5 parts of unsaturated monobasic acid; 0.002-0.22 parts of curing agent; 0.001-0.18 parts of accelerator; 0.051 parts of photoinitiator; and 0.2-4 parts of dispersant.
[0032] Preferably, the reactive asphalt cold patch material comprises the following components, in parts by weight: 92 parts of aggregate; 2 parts of mineral powder; 0.5 parts of filler; 2 parts of diffusion oil; and 6 parts of asphalt cold patch liquid.
[0033] The asphalt cold patching liquid is composed of the following components in parts by weight: 72 parts of base asphalt; 28 parts of unsaturated polyester resin; 0.3 parts of unsaturated monobasic acid; 0.12 parts of curing agent; 0.12 parts of accelerator; 0.051 parts of photoinitiator; and 3 parts of dispersant.
[0034] Preferably, the aggregate composition is as follows: 4.75-9.5 mm stone accounts for 55-75% of the total mass of all aggregates, 2.36-4.75 mm stone accounts for 15-25% of the total mass of all aggregates, and 1.75-2.36 mm stone accounts for 4%-15% of the total mass of all aggregates; stone refers to rocks that are mined and processed and used for infrastructure such as buildings, roads, bridges, etc. It can be natural rock (such as granite, sandstone, limestone) or artificial crushed stone.
[0035] The mineral powder is S95 grade granulated blast furnace slag powder; granulated blast furnace slag powder is a kind of fine powder material made by quenching the slag produced in the ironmaking process to form glass particles, and then drying and grinding. It is widely used in cement, concrete and other building materials as a high-efficiency mineral admixture. According to my country's national standard "GB / T18046-2008" (granulated blast furnace slag powder used in cement and concrete), S95 grade slag powder must meet the following quality indicators: Density: ≥2.8g / cm 3 Specific surface area: ≥400m 2 / kg, activity index: 7 days: ≥75%. 28 days: ≥95%. Fluidity ratio: ≥95%. Water content: ≤1.0%. Loss on ignition: ≤1.0%. Sulfur trioxide (SO3) content: ≤4.0%. Chloride ion content: ≤0.06%. Insoluble matter content: ≤3.0%. Glass content: ≥85%.
[0036] The filler is waste glass fiber, the length of the glass fiber is 3mm-10mm, and the diameter of the glass fiber is 200-600um; the waste glass fiber mainly comes from the scraps in industrial production, scrapped FRP products (such as pipes, storage tanks, hulls, etc.) or other composite materials containing glass fiber. After mechanical crushing, cutting and other methods, glass fibers with a specific length and diameter range are obtained.
[0037] The diffusion oil is silicone oil, and its CAS number is 63148-58-3. Appearance: light yellow transparent liquid, odorless. Density: about 1.05g / cm 3 .
[0038] Preferably, the base asphalt is 70# base asphalt; 70# base asphalt refers to road petroleum asphalt with a needle penetration of 60-80 (0.1mm). Characteristics: Needle penetration: 60-80 (0.1mm), indicating the penetration depth of asphalt at 25°C, 5s, and 100g load. Softening point: ≥46°C, indicating the temperature of asphalt when it falls 25.4mm when heated. Dynamic viscosity at 60°C: ≥180Pa·s, ensuring sufficient viscosity at high temperatures. Elongation at 10°C: ≥15cm, ductility at low temperatures. Elongation at 15°C: ≥100cm, ductility at room temperature. Wax content: ≤2.2%, reducing the brittleness of asphalt. Flash point: ≥260°C, ensuring safety. Solubility: ≥99.5%, indicating the solubility of asphalt in solvents. Density: measured and recorded, usually about 1.05g / cm 3 .
[0039] The unsaturated polyester resin is 3198 type resin or 196 type resin, wherein the CAS number of 3198 type resin is 25037-66-5, and the CAS number of 196 type resin is 26098-37-3.
[0040] The molecular formula of 3198 unsaturated polyester resin is: C 15 H 14 O8, molecular weight: 322.27, appearance: light yellow transparent viscous liquid. Solid content: 70%. Acid value: 18mgKOH / g.
[0041] The appearance of 196 type unsaturated polyester resin is light yellow transparent viscous liquid, solid content: 64%, acid value: 25mgKOH / g.
[0042] The unsaturated monoacid is acrylic acid, oleic acid or linoleic acid.
[0043] Acrylic Acid Molecular weight: 72.063, Appearance: Colorless liquid with pungent odor, Melting point: 13°C, Boiling point: 140.9°C, Density: 1.051 g / cm 3 , Flash point: 54°C, Solubility: Easily soluble in water.
[0044] Oleic Acid Molecular weight: 282.46, Appearance: Colorless to light yellow oily liquid, Melting point: 13.4℃, Boiling point: 360℃, Density: 0.895g / cm 3 , Flash point: 189℃, Water solubility: insoluble in water, soluble in most organic solvents.
[0045] Linoleic Acid Molecular weight: 280.44, Appearance: Light yellow oily liquid, Melting point: -5°C, Boiling point: 360.6°C, Density: 0.902 g / cm 3, Flash point: 273℃, Water solubility: insoluble in water, soluble in most organic solvents.
[0046] The curing agent is methyl ethyl ketone peroxide (CAS No.: 1338-23-4), cyclohexanone peroxide (CAS No.: 78-18-2) or acetylacetone peroxide (CAS No.: 37187-22-7).
[0047] Methyl ethyl ketone peroxide molecular weight: 210.225, appearance: colorless transparent liquid with pleasant odor, melting point: 110℃, boiling point: 284℃, density: 1.053g / cm 3 , Flash point: 50℃, Water solubility: slightly soluble in water, soluble in alcohol, ether and ester.
[0048] Cyclohexanone peroxide molecular weight: 246.30, appearance: light yellow needle-shaped powder, melting point: 76°C, boiling point: 374.7°C, density: 1.2g / cm 3 , Water solubility: insoluble in water, soluble in acetone, ethanol, petroleum ether and acid.
[0049] Acetylacetone peroxide molecular weight: 132.11, appearance: light yellow transparent liquid, melting point: -23°C, boiling point: 140.4°C, density: 0.975 g / mL.
[0050] The promoter is cobalt isooctanoate, cobalt cyclohexaneate or sodium dodecyl sulfonate.
[0051] Cobalt 2-ethylhexanoate CAS number: 136-52-7, molecular weight: 345.34, appearance: purple liquid, density: 1.002g / mL, water solubility: 40.3g / L,
[0052] Cobalt naphthenate CAS number: 61789-51-3, appearance: light blue-red solid.
[0053] Sodium dodecyl sulfate CAS number: 2386-53-0, molecular weight: 272.38, appearance: white fine crystals, melting point: >300℃.
[0054] The photoinitiator is nano-modified benzoin dimethyl ether.
[0055] Benzoin dimethyl ether molecular weight: 256.30, CAS number: 24650-42-8, EINECS number: 246-386-2, appearance: white powder, density: 1.1±0.1g / cm 3 .
[0056] The dispersant is alkylene glycidyl ether, polypropylene glycol diglycidyl ether or o-cresyl glycidyl ether.
[0057] Alkylene glycidyl ether CAS number: 68609-97-2, molecular weight: 769.27, appearance: colorless, odorless, transparent liquid, density: 0.89g / mL.
[0058] Polypropylene glycol diglycidyl ether CAS number: 26142-30-3, Appearance: light yellow transparent liquid, Density: 1.05±0.01g / mL.
[0059] o-Cresyl glycidyl ether CAS number: 2210-79-9, molecular weight: 164.20, appearance: transparent light yellow liquid, density: 1.079 g / mL.
[0060] Preferably, the preparation method of nano-modified benzoin dimethyl ether is as follows: dissolve benzoin dimethyl ether in 10% acetic acid aqueous solution with a mass percentage of ten times the weight, continue to add glutamic acid with a weight of 0.2 times the weight of benzoin dimethyl ether, stir and mix thoroughly, then add ferrocenecarboxylic acid with a weight of 0.01 times the weight of benzoin dimethyl ether, stir and mix thoroughly, transfer to a reactor and react at 65°C for 2h-6h to obtain. Wherein ferrocenecarboxylic acid has a molecular weight of 230.04, CAS number: 1271-42-7, appearance: yellow crystal, odorless, melting point: 210°C, density: 1.862g / cm 3 , Solubility: Insoluble in water, soluble in organic solvents (such as chloroform, DMSO, methanol, etc.).
[0061] The method for preparing the reactive asphalt cold patch material comprises the following steps: (1) drying the aggregate at 105°C to constant weight and then cooling to room temperature for use; (2) weighing the aggregate, mineral powder, filler, diffusion oil and asphalt cold patch liquid respectively; (3) adding the weighed aggregate and filler into a mixer and stirring them thoroughly; (4) adding diffusion oil to the mixture obtained in step (3) and continuing to stir, adding asphalt cold patch liquid and stirring again after stirring, then adding mineral powder and continuing to stir until the mixture is formed; (5) putting the mixture obtained in step (4) into a sealed bag and avoiding direct sunlight.
[0062] Preferably, in step (1), the aggregate is spread flat on a baking tray, placed in an oven at 105±5°C for drying, turned over and weighed every 1 hour, and a constant weight is considered to be reached when the difference between the two weighings is less than 0.1%. The dried aggregate is then taken out, naturally cooled to room temperature (20±5°C) and kept in a dry state for use to avoid moisture absorption or secondary contamination.
[0063] Preferably, in step (3), the weighed aggregate and filler are added to a mixer together, first stirred at a low speed of 40-60 r / min for 30-60 s to initially disperse the aggregate and filler, and then stirred at a medium speed of 70-100 r / min for 60-90 s until the two are fully and evenly mixed.
[0064] Preferably, in step (4), diffusion oil is slowly added to the mixture obtained in step (3), and the mixture is stirred at a speed of 40-60 r / min for 30-60 s to fully disperse the diffusion oil in the mixture, and then the mixture is stirred at a speed of 70-100 r / min for 30-60 s; after the diffusion oil is evenly dispersed, asphalt cold make-up liquid is added, and the mixture is stirred at a speed of 70-100 r / min for 60-90 s; then mineral powder is added to the mixture, and the mixture is stirred at a speed of 70-100 r / min for 60-90 s until the mixture is formed.
[0065] Beneficial Effects
[0066] Compared with the prior art, the beneficial effects of the present invention are: energy saving and environmental protection, convenient construction: the cold patch material can be constructed at room temperature without heating, avoiding the need for high-temperature heating of traditional hot-mix asphalt mixtures, and significantly reducing energy consumption and carbon emissions.
[0067] The construction process is simple. You only need to spread the mixture on the area that needs to be repaired and quickly solidify it into shape through light-curing technology, which greatly shortens the maintenance time.
[0068] High strength and durability: Through the synergistic effect of unsaturated polyester resin, unsaturated monobasic acid, curing agent and accelerator, the cold patch material can be quickly cured under light conditions to form a dense cross-linked structure.
[0069] Cold patch material has excellent early strength and durability, can withstand long-term traffic loads, and reduce the frequency of subsequent maintenance.
[0070] Excellent bonding performance: The addition of unsaturated monobasic acids (such as acrylic acid, oleic acid or linoleic acid) improves the bonding between the cold patch material and the original pavement material, ensuring the integrity and stability of the repaired material.
[0071] Improved construction and workability: The use of diffusion oil (such as silicone oil) improves the fluidity of the cold patch material, making the components mixed more evenly and improving the ease of operation during construction.
[0072] Dispersants (such as alkylene glycidyl ether, polypropylene glycol diglycidyl ether, etc.) enhance the dispersion stability of the system and ensure the consistency of material performance.
[0073] High storage stability: Cold patch materials can effectively avoid direct sunlight when sealed, preventing the system from reacting prematurely, thus having good storage stability and being suitable for long-term storage and transportation.
[0074] Rapid curing and improved repair efficiency: Photoinitiators (such as nano-modified benzoin dimethyl ether) initiate polymerization reactions under ultraviolet or visible light, causing the cold patch material to cure rapidly, greatly shortening the road closure time and reducing the impact on traffic.
[0075] Optimization of material performance: The aggregate adopts reasonable grading (such as 4.75-9.5mm accounting for 55-75%, 2.36-4.75mm accounting for 15-25%, 1.75-2.36mm accounting for 4%-15%), combined with S95 grade granulated blast furnace slag powder as mineral powder filling, which improves the compressive strength and durability of the material.
[0076] Using waste glass fiber as filler not only enhances the toughness of the material, but also realizes the resource utilization of waste, which is in line with the development direction of green building materials.
[0077] Significant economic and social benefits: The present invention solves the problems of low early strength and poor durability of traditional cold patch materials, while reducing construction costs and environmental pollution, providing a new type of efficient, environmentally friendly and economical material for road repair.
[0078] In summary, the reactive asphalt cold patch material and the preparation method thereof of the present invention are superior to the prior art in terms of performance, environmental protection and construction efficiency, and have broad application prospects in the field of road repair. DETAILED DESCRIPTION
[0079] The present invention is further described below in conjunction with specific embodiments.
[0080] Unless otherwise defined, the technical and scientific terms used in the following examples have the same meanings as commonly understood by those skilled in the art to which the present invention belongs. In practical application, the weight parts referred to in the present invention can be set as the unit kilogram.
[0081] Example 1
[0082] The reactive asphalt cold patch material, calculated in parts by weight, has the following components: 90 parts of aggregate; 3 parts of mineral powder; 0.2 parts of filler; 3.0 parts of diffusion oil; and 4 parts of asphalt cold patch liquid.
[0083] The asphalt cold patching liquid is composed of the following components in parts by weight: 60 parts of base asphalt; 38 parts of unsaturated polyester resin; 0.05 parts of unsaturated monobasic acid; 0.22 parts of curing agent; 0.001 parts of accelerator; 0.051 parts of photoinitiator; and 0.2 parts of dispersant.
[0084] The aggregate components are as follows: 4.75-9.5mm stone accounts for 55-75% of the total mass of all aggregates, 2.36-4.75mm stone accounts for 15-25% of the total mass of all aggregates, and 1.75-2.36mm stone accounts for 4%-15% of the total mass of all aggregates.
[0085] The slag powder is S95 grade granulated blast furnace slag powder.
[0086] The filler is waste glass fiber, the length of the glass fiber is 3 mm, and the diameter of the glass fiber is 600 um.
[0087] The diffusion oil is silicone oil, and its CAS number is 63148-58-3.
[0088] The base asphalt is 70# base asphalt.
[0089] The unsaturated polyester resin is 3198 type resin, and the CAS number of 3198 type resin is 25037-66-5.
[0090] The unsaturated monoacid is acrylic acid.
[0091] The curing agent is methyl ethyl ketone peroxide.
[0092] The accelerator is cobalt octanoate.
[0093] The photoinitiator is nano-modified benzoin dimethyl ether.
[0094] The dispersant is alkylene glycidyl ether.
[0095] The preparation method of nano-modified benzoin dimethyl ether is as follows: dissolve benzoin dimethyl ether in 10% acetic acid aqueous solution with a mass percentage of ten times the weight, continue to add glutamic acid with a weight of 0.2 times the weight of benzoin dimethyl ether, stir and mix thoroughly, then add ferrocenecarboxylic acid with a weight of 0.01 times the weight of benzoin dimethyl ether, stir and mix thoroughly, transfer to a reactor and react at 65°C for 2h to obtain the product.
[0096] The method for preparing the reactive asphalt cold patch material comprises the following steps: (1) drying the aggregate at 105°C to constant weight and then cooling to room temperature for use; (2) weighing the aggregate, mineral powder, filler, diffusion oil and asphalt cold patch liquid respectively; (3) adding the weighed aggregate and filler into a mixer and stirring them thoroughly; (4) adding diffusion oil to the mixture obtained in step (3) and continuing to stir, adding asphalt cold patch liquid and stirring again after stirring, then adding mineral powder and continuing to stir until the mixture is formed; (5) putting the mixture obtained in step (4) into a sealed bag and avoiding direct sunlight.
[0097] In step (1), the aggregate is spread flat on a baking tray, placed in an oven at 105±5°C for drying, turned over and weighed every 1 hour, and a constant weight is considered to be reached when the difference between the two weighings is less than 0.1%. The dried aggregate is then taken out, naturally cooled to room temperature (20±5°C) and kept dry for use to avoid moisture absorption or secondary contamination.
[0098] In step (3), the weighed aggregate and filler are added into the mixer together, first stirred at a low speed of 40 r / min for 60 s to make the aggregate and filler dispersed initially, and then stirred at a medium speed of 70 r / min for 90 s until the two are fully and evenly mixed.
[0099] In step (4), the diffusion oil is slowly added to the mixture obtained in step (3), and the mixture is stirred at a speed of 40 r / min for 60 seconds to fully disperse the diffusion oil in the mixture, and then the stirring is continued at a speed of 70 r / min for 60 seconds; after the diffusion oil is evenly dispersed, the asphalt cold make-up liquid is added, and the mixture is stirred at a speed of 70 r / min for 90 seconds; then, the mineral powder is added to the mixture, and the mixture is stirred at a speed of 70 r / min for 90 seconds until the mixture is formed.
[0100] Example 2
[0101] The reactive asphalt cold patch material, calculated in parts by weight, has the following components: 94 parts of aggregate; 1 part of mineral powder; 0.7 parts of filler; 0.5 parts of diffusion oil; and 8 parts of asphalt cold patch liquid.
[0102] The asphalt cold patching liquid is composed of the following components in parts by weight: 88 parts of base asphalt; 12 parts of unsaturated polyester resin; 0.5 parts of unsaturated monobasic acid; 0.002 parts of curing agent; 0.18 parts of accelerator; 0.051 parts of photoinitiator; and 4 parts of dispersant.
[0103] The aggregate components are as follows: 4.75-9.5mm stone accounts for 55-75% of the total mass of all aggregates, 2.36-4.75mm stone accounts for 15-25% of the total mass of all aggregates, and 1.75-2.36mm stone accounts for 4%-15% of the total mass of all aggregates.
[0104] The slag powder is S95 grade granulated blast furnace slag powder.
[0105] The filler is waste glass fiber, the length of the glass fiber is 10 mm, and the diameter of the glass fiber is 200 um.
[0106] The diffusion oil is silicone oil, and its CAS number is 63148-58-3.
[0107] The base asphalt is 70# base asphalt.
[0108] The unsaturated polyester resin is 196 type resin, and the CAS number of 196 type resin is 26098-37-3.
[0109] Among them, the unsaturated monobasic acid is oleic acid.
[0110] The curing agent is cyclohexanone peroxide.
[0111] The promoter is cobalt cyclohexaneate.
[0112] The photoinitiator is nano-modified benzoin dimethyl ether.
[0113] The dispersant is polypropylene glycol diglycidyl ether.
[0114] The preparation method of nano-modified benzoin dimethyl ether is as follows: dissolve benzoin dimethyl ether in 10% acetic acid aqueous solution with a mass percentage of ten times the weight, continue to add glutamic acid with a weight of 0.2 times the weight of benzoin dimethyl ether, stir and mix thoroughly, then add ferrocenecarboxylic acid with a weight of 0.01 times the weight of benzoin dimethyl ether, stir and mix thoroughly, transfer to a reactor and react at 65°C for 6 hours to obtain the product.
[0115] The method for preparing the reactive asphalt cold patch material comprises the following steps: (1) drying the aggregate at 105°C to constant weight and then cooling to room temperature for use; (2) weighing the aggregate, mineral powder, filler, diffusion oil and asphalt cold patch liquid respectively; (3) adding the weighed aggregate and filler into a mixer and stirring them thoroughly; (4) adding diffusion oil to the mixture obtained in step (3) and continuing to stir, adding asphalt cold patch liquid and stirring again after stirring, then adding mineral powder and continuing to stir until the mixture is formed; (5) putting the mixture obtained in step (4) into a sealed bag and avoiding direct sunlight.
[0116] In step (1), the aggregate is spread flat on a baking tray, placed in an oven at 105±5°C for drying, turned over and weighed every 1 hour, and a constant weight is considered to be reached when the difference between the two weighings is less than 0.1%. The dried aggregate is then taken out, naturally cooled to room temperature (20±5°C) and kept dry for use to avoid moisture absorption or secondary contamination.
[0117] In step (3), the weighed aggregate and filler are added into the mixer together, first stirred at a low speed of 60 r / min for 30 s to make the aggregate and filler dispersed initially, and then stirred at a medium speed of 100 r / min for 60 s until the two are fully and evenly mixed.
[0118] In step (4), the diffusion oil is slowly added to the mixture obtained in step (3), and the mixture is stirred at a speed of 60 r / min for 30 seconds to fully disperse the diffusion oil in the mixture, and then the stirring is continued at a speed of 100 r / min for 30 seconds; after the diffusion oil is evenly dispersed, the asphalt cold make-up liquid is added and stirred at a speed of 100 r / min for 60 seconds; then the mineral powder is added to the mixture, and the stirring is continued at a speed of 100 r / min for 60 seconds until the mixture is formed.
[0119] Example 3
[0120] The reactive asphalt cold patch material, calculated in parts by weight, has the following components: 92 parts of aggregate; 2 parts of mineral powder; 0.5 parts of filler; 2 parts of diffusion oil; and 6 parts of asphalt cold patch liquid.
[0121] The asphalt cold patching liquid is composed of the following components in parts by weight: 72 parts of base asphalt; 28 parts of unsaturated polyester resin; 0.3 parts of unsaturated monobasic acid; 0.12 parts of curing agent; 0.12 parts of accelerator; 0.051 parts of photoinitiator; and 3 parts of dispersant.
[0122] The aggregate components are as follows: 4.75-9.5mm stone accounts for 55-75% of the total mass of all aggregates, 2.36-4.75mm stone accounts for 15-25% of the total mass of all aggregates, and 1.75-2.36mm stone accounts for 4%-15% of the total mass of all aggregates.
[0123] The slag powder is S95 grade granulated blast furnace slag powder.
[0124] The filler is waste glass fiber, the length of the glass fiber is 5 mm, and the diameter of the glass fiber is 400 um.
[0125] The diffusion oil is silicone oil, and its CAS number is 63148-58-3.
[0126] The base asphalt is 70# base asphalt.
[0127] The unsaturated polyester resin is 196 type resin, and the CAS number of 196 type resin is 26098-37-3.
[0128] Among them, the unsaturated monobasic acid is linoleic acid.
[0129] The curing agent is acetylacetone peroxide.
[0130] The accelerator is sodium dodecyl sulfate.
[0131] The photoinitiator is nano-modified benzoin dimethyl ether.
[0132] The dispersant is o-cresyl glycidyl ether.
[0133] The preparation method of nano-modified benzoin dimethyl ether is as follows: dissolve benzoin dimethyl ether in 10% acetic acid aqueous solution with a mass percentage of ten times the weight, continue to add glutamic acid with a weight of 0.2 times the weight of benzoin dimethyl ether, stir and mix thoroughly, then add ferrocenecarboxylic acid with a weight of 0.01 times the weight of benzoin dimethyl ether, stir and mix thoroughly, transfer to a reactor and react at 65°C for 4 hours to obtain the product.
[0134] The method for preparing the reactive asphalt cold patch material comprises the following steps: (1) drying the aggregate at 105°C to constant weight and then cooling to room temperature for use; (2) weighing the aggregate, mineral powder, filler, diffusion oil and asphalt cold patch liquid respectively; (3) adding the weighed aggregate and filler into a mixer and stirring them thoroughly; (4) adding diffusion oil to the mixture obtained in step (3) and continuing to stir, adding asphalt cold patch liquid and stirring again after stirring, then adding mineral powder and continuing to stir until the mixture is formed; (5) putting the mixture obtained in step (4) into a sealed bag and avoiding direct sunlight.
[0135] In step (1), the aggregate is spread flat on a baking tray, placed in an oven at 105±5°C for drying, turned over and weighed every 1 hour, and a constant weight is considered to be reached when the difference between the two weighings is less than 0.1%. The dried aggregate is then taken out, naturally cooled to room temperature (20±5°C) and kept dry for use to avoid moisture absorption or secondary contamination.
[0136] In step (3), the weighed aggregate and filler are added into the mixer together, first stirred at a low speed of 50 r / min for 50 s to initially disperse the aggregate and filler, and then stirred at a medium speed of 90 r / min for 80 s until the two are fully and evenly mixed.
[0137] In step (4), the diffusion oil is slowly added to the mixture obtained in step (3), and the mixture is stirred at a speed of 50 r / min for 50 seconds to fully disperse the diffusion oil in the mixture, and then the mixture is stirred at a speed of 80 r / min for 50 seconds; after the diffusion oil is evenly dispersed, the asphalt cold make-up liquid is added, and the mixture is stirred at a speed of 80 r / min for 80 seconds; then the mineral powder is added to the mixture, and the mixture is stirred at a speed of 80 r / min for 80 seconds until the mixture is formed.
[0138] Comparative Example 1
[0139] The reactive asphalt cold patch material, calculated in parts by weight, has the following components: 92 parts of aggregate; 2 parts of mineral powder; 0.5 parts of filler; and 2 parts of diffusion oil.
[0140] The asphalt cold patching liquid is composed of the following components in parts by weight: 72 parts of base asphalt; 28 parts of unsaturated polyester resin; 0.3 parts of unsaturated monobasic acid; 0.12 parts of curing agent; 0.12 parts of accelerator; 0.051 parts of photoinitiator; and 3 parts of dispersant.
[0141] The aggregate components are as follows: 4.75-9.5mm stone accounts for 55-75% of the total mass of all aggregates, 2.36-4.75mm stone accounts for 15-25% of the total mass of all aggregates, and 1.75-2.36mm stone accounts for 4%-15% of the total mass of all aggregates.
[0142] The slag powder is S95 grade granulated blast furnace slag powder.
[0143] The filler is waste glass fiber, the length of the glass fiber is 5 mm, and the diameter of the glass fiber is 400 um.
[0144] The diffusion oil is silicone oil, and its CAS number is 63148-58-3.
[0145] The base asphalt is 70# base asphalt.
[0146] The unsaturated polyester resin is 196 type resin, and the CAS number of 196 type resin is 26098-37-3.
[0147] Among them, the unsaturated monobasic acid is linoleic acid.
[0148] The curing agent is acetylacetone peroxide.
[0149] The accelerator is sodium dodecyl sulfate.
[0150] The photoinitiator is benzoin dimethyl ether.
[0151] The dispersant is o-cresyl glycidyl ether.
[0152] The method for preparing the reactive asphalt cold patch material comprises the following steps: (1) drying the aggregate at 105°C to constant weight and then cooling to room temperature for use; (2) weighing the aggregate, mineral powder, filler, diffusion oil and asphalt cold patch liquid respectively; (3) adding the weighed aggregate and filler into a mixer and stirring them thoroughly; (4) adding diffusion oil to the mixture obtained in step (3) and continuing to stir, adding asphalt cold patch liquid and stirring again after stirring, then adding mineral powder and continuing to stir until the mixture is formed; (5) putting the mixture obtained in step (4) into a sealed bag and avoiding direct sunlight.
[0153] In step (1), the aggregate is spread flat on a baking tray, placed in an oven at 105±5°C for drying, turned over and weighed every 1 hour, and a constant weight is considered to be reached when the difference between the two weighings is less than 0.1%. The dried aggregate is then taken out, naturally cooled to room temperature (20±5°C) and kept dry for use to avoid moisture absorption or secondary contamination.
[0154] In step (3), the weighed aggregate and filler are added into the mixer together, first stirred at a low speed of 50 r / min for 50 s to initially disperse the aggregate and filler, and then stirred at a medium speed of 90 r / min for 80 s until the two are fully and evenly mixed.
[0155] In step (4), the diffusion oil is slowly added to the mixture obtained in step (3), and the mixture is stirred at a speed of 50 r / min for 50 seconds to fully disperse the diffusion oil in the mixture, and then the mixture is stirred at a speed of 80 r / min for 50 seconds; after the diffusion oil is evenly dispersed, the asphalt cold make-up liquid is added, and the mixture is stirred at a speed of 80 r / min for 80 seconds; then the mineral powder is added to the mixture, and the mixture is stirred at a speed of 80 r / min for 80 seconds until the mixture is formed.
[0156] Comparative Example 2
[0157] The reactive asphalt cold patch material, calculated in parts by weight, has the following components: 92 parts of aggregate; 2 parts of mineral powder; 0.5 parts of filler; 2 parts of diffusion oil; and 6 parts of asphalt cold patch liquid.
[0158] The asphalt cold patching liquid is composed of the following components in parts by weight: 72 parts of base asphalt; 0.3 parts of unsaturated monobasic acid; 0.12 parts of curing agent; 0.12 parts of accelerator; 0.051 parts of photoinitiator; and 3 parts of dispersant.
[0159] The aggregate components are as follows: 4.75-9.5mm stone accounts for 55-75% of the total mass of all aggregates, 2.36-4.75mm stone accounts for 15-25% of the total mass of all aggregates, and 1.75-2.36mm stone accounts for 4%-15% of the total mass of all aggregates.
[0160] The slag powder is S95 grade granulated blast furnace slag powder.
[0161] The filler is waste glass fiber, the length of the glass fiber is 5 mm, and the diameter of the glass fiber is 400 um.
[0162] The diffusion oil is silicone oil, and its CAS number is 63148-58-3.
[0163] The base asphalt is 70# base asphalt.
[0164] Among them, the unsaturated monobasic acid is linoleic acid.
[0165] The curing agent is acetylacetone peroxide.
[0166] The accelerator is sodium dodecyl sulfate.
[0167] The photoinitiator is nano-modified benzoin dimethyl ether.
[0168] The dispersant is o-cresyl glycidyl ether.
[0169] The preparation method of nano-modified benzoin dimethyl ether is as follows: dissolve benzoin dimethyl ether in 10% acetic acid aqueous solution with a mass percentage of ten times the weight, continue to add glutamic acid with a weight of 0.2 times the weight of benzoin dimethyl ether, stir and mix thoroughly, then add ferrocenecarboxylic acid with a weight of 0.01 times the weight of benzoin dimethyl ether, stir and mix thoroughly, transfer to a reactor and react at 65°C for 4 hours to obtain the product.
[0170] The method for preparing the reactive asphalt cold patch material comprises the following steps: (1) drying the aggregate at 105°C to constant weight and then cooling to room temperature for use; (2) weighing the aggregate, mineral powder, filler, diffusion oil and asphalt cold patch liquid respectively; (3) adding the weighed aggregate and filler into a mixer and stirring them thoroughly; (4) adding diffusion oil to the mixture obtained in step (3) and continuing to stir, adding asphalt cold patch liquid and stirring again after stirring, then adding mineral powder and continuing to stir until the mixture is formed; (5) putting the mixture obtained in step (4) into a sealed bag and avoiding direct sunlight.
[0171] In step (1), the aggregate is spread flat on a baking tray, placed in an oven at 105±5°C for drying, turned over and weighed every 1 hour, and a constant weight is considered to be reached when the difference between the two weighings is less than 0.1%. The dried aggregate is then taken out, naturally cooled to room temperature (20±5°C) and kept dry for use to avoid moisture absorption or secondary contamination.
[0172] In step (3), the weighed aggregate and filler are added into the mixer together, first stirred at a low speed of 50 r / min for 50 s to initially disperse the aggregate and filler, and then stirred at a medium speed of 90 r / min for 80 s until the two are fully and evenly mixed.
[0173] In step (4), the diffusion oil is slowly added to the mixture obtained in step (3), and the mixture is stirred at a speed of 50 r / min for 50 seconds to fully disperse the diffusion oil in the mixture, and then the mixture is stirred at a speed of 80 r / min for 50 seconds; after the diffusion oil is evenly dispersed, the asphalt cold make-up liquid is added, and the mixture is stirred at a speed of 80 r / min for 80 seconds; then the mineral powder is added to the mixture, and the mixture is stirred at a speed of 80 r / min for 80 seconds until the mixture is formed.
[0174] Test Case
[0175] Initial Marshall stability: Weigh the formed asphalt cold patch material, compact it 50 times on both sides at 20°C, control the specimen height at 63.5±1.3mm, and test it immediately.
[0176] Final Marshall stability: Tested in accordance with JT / T972-2015 (Asphalt pavement pothole cold patch finished material).
[0177] Adhesion: Tested in accordance with JTGE20-2019 (Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering).
[0178] Residual stability: Tested in accordance with JTGE20-2019 (Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering).
[0179] Rutting test: Test in accordance with JTGE20-2019 (Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering).
[0180] Penetration strength: Tested in accordance with JT / T972-2015 (Asphalt pavement pothole cold patch finished materials).
[0181] Strength growth: Curing was carried out at 20°C, and the Marshall stability was tested at 2h, 4h, 1d, 3d, 7d, and 28d.
[0182] The performance test results are shown in Table 1 and Table 2 below:
[0183] Table 1 Basic performance test table
[0184]
[0185] Table 2 Strength growth test table
[0186]
[0187] Technical effect analysis: initial forming Marshall stability: the initial forming stability of Examples 1-3 is higher than that of Comparative Examples 1-2, indicating that the formula of the examples has higher stability at the initial stage.
[0188] Final forming Marshall stability: The final forming stability of Examples 1-3 is also significantly higher than that of Comparative Examples 1-2, indicating that the materials of the Examples have higher stability and durability after curing.
[0189] Adhesion: The adhesion of Examples 1-3 is higher than that of Comparative Examples 1-2, indicating that the materials of the Examples have better adhesion to the base material, reducing the risk of peeling and detachment.
[0190] Residual stability: The residual stability of Examples 1-3 is higher than that of Comparative Examples 1-2, indicating that the materials of the Examples maintain better stability in long-term use.
[0191] Rutting test: The rutting test results of Examples 1-3 are relatively low, indicating that the materials of the Examples have better rutting resistance at high temperatures and reduce road surface deformation.
[0192] Penetration strength: The penetration strength of Examples 1-3 is relatively low, indicating that the materials of the Examples have better compressive strength and reduce the risk of the road surface being pressed into.
[0193] Strength growth: The strength growth of Examples 1-3 in each curing period is higher than that of Comparative Examples 1-2, especially after 7d and 28d, the strength growth is significant, indicating that the materials of the Examples can quickly reach high strength during the curing process, thereby improving the construction efficiency and the durability of the pavement.
[0194] Conclusion: The formulations of Examples 1-3 are superior to those of Comparative Examples 1-2 in all performance indicators, showing higher stability, better adhesion, lower rutting depth and higher compressive strength.
[0195] The material of the embodiment has a rapid strength increase during the curing process, and the time to reach high strength is short, which is suitable for rapid construction and repair. These technical effects show that the formula and preparation method of the embodiment have significant advantages in the treatment of water leakage and can improve the construction efficiency and quality of underground projects.
[0196] Comparative Example 1 uses unmodified benzoin dimethyl ether, while the nano-modified benzoin dimethyl ether has significantly enhanced permeability compared to the unmodified benzoin dimethyl ether. This improvement is mainly due to the following mechanisms: First, glutamic acid can form stable chemical bonds with benzoin dimethyl ether molecules, significantly improving the stability and durability of the material. At the same time, the introduction of glutamic acid further reduces the intermolecular hindrance, making it easier for benzoin dimethyl ether to penetrate into the tiny cracks and pores in the asphalt cold patch material, thereby improving its permeability. In addition, ferrocenecarboxylic acid, as an organic metal compound, plays a dual role in this system: on the one hand, it provides antioxidant and UV resistance through its metal center, effectively extending the service life of the material in harsh environments; on the other hand, ferrocenecarboxylic acid can reduce the viscosity of benzoin dimethyl ether, thereby further enhancing its permeability. This reduction in viscosity makes it easier for the material to flow and fill cracks during construction, improving the overall repair effect. The acetic acid aqueous solution acts as a catalyst to accelerate the chemical reaction between benzoin dimethyl ether, glutamic acid and ferrocenecarboxylic acid; through the catalytic effect, it not only shortens the curing time but also significantly improves the construction efficiency; this process ensures that the material can form a stable and high-strength cross-linked structure while curing quickly.
[0197] In summary, nano-modified benzoin dimethyl ether has achieved the following performance improvements by introducing glutamic acid and ferrocenecarboxylic acid and with the help of the catalytic effect of aqueous acetic acid solution: Permeability: significantly enhanced, able to better fill tiny cracks and pores.
[0198] Reaction speed: speed up the curing process and improve construction efficiency.
[0199] Stability and durability: Form a more stable molecular structure and extend the life of the material.
[0200] Environmental protection: Maintain non-toxic and harmless characteristics, in line with the requirements of green building materials.
[0201] These improvements enable nano-modified benzoin dimethyl ether to demonstrate excellent performance in the treatment of water leakage problems, effectively solving the limitations of traditional benzoin dimethyl ether in practical applications, such as insufficient permeability and slow reaction speed, and providing a new efficient and environmentally friendly solution for underground engineering repair.
[0202] Comparative Example 2 removes the unsaturated polyester resin. However, since the unsaturated polyester resin (UPR) is a commonly used thermosetting resin with good mechanical properties, corrosion resistance and processing properties, its removal leads to a decrease in the overall performance of the product.
[0203] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field of energy-saving and environmentally friendly building materials technology to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope determined by the claims submitted by the present invention.
Claims
1. A reactive asphalt cold patch material, characterized in that: The components are as follows in parts by weight: 90-94 parts of aggregate; 1-3 parts of mineral powder; 0.2-0.7 parts of filler; 0.5-3.0 parts of diffusion oil; 4-8 parts of asphalt cold repair liquid; wherein the filler is waste glass fiber, wherein the asphalt cold repair liquid is composed of the following components in parts by weight: 60-88 parts of matrix asphalt; 12-38 parts of unsaturated polyester resin; 0.05-0.5 parts of unsaturated monobasic acid; 0.002-0.22 parts of curing agent; 0.001-0.18 parts of accelerator; photoinitiator 0.051 parts of agent; 0.2-4 parts of dispersant; wherein the photoinitiator is nano-modified benzoin dimethyl ether; wherein the preparation method of the nano-modified benzoin dimethyl ether is as follows: dissolve benzoin dimethyl ether in 10 times the weight of 10% acetic acid aqueous solution, continue to add glutamic acid in an amount of 0.2 times the weight of benzoin dimethyl ether, stir and mix thoroughly, then add ferrocenecarboxylic acid in an amount of 0.01 times the weight of benzoin dimethyl ether, stir and mix thoroughly, transfer to a reactor and react at 65°C for 2h-6h to obtain.
2. The reactive asphalt cold patch material according to claim 1, characterized in that: The components are as follows in parts by weight: 92 parts of aggregate; 2 parts of mineral powder; 0.5 parts of filler; 2 parts of diffusion oil; 6 parts of asphalt cold repair liquid; wherein the asphalt cold repair liquid is composed of the following components in parts by weight: 72 parts of base asphalt; 28 parts of unsaturated polyester resin; 0.3 parts of unsaturated monobasic acid; 0.12 parts of curing agent; 0.12 parts of accelerator; 0.051 parts of photoinitiator; 3 parts of dispersant.
3. The reactive asphalt cold patch material according to claim 2, characterized in that: The aggregate components are as follows: 4.75-9.5 mm stone accounts for 55-75% of the total mass of all aggregates, 2.36-4.75 mm stone accounts for 15-25% of the total mass of all aggregates, 1.75-2.36 mm stone accounts for 4%-15% of the total mass of all aggregates, and the sum of the mass fractions of 4.75-9.5 mm stone, 2.36-4.75 mm stone and 1.75-2.36 mm stone in the total aggregate is 100%; the mineral powder is S95 grade granulated blast furnace slag powder; the length of the waste glass fiber is 3mm-10mm, and the diameter of the waste glass fiber is 200-600um; the diffusion oil is silicone oil, and its CAS number is 63148-58-3.
4. The reactive asphalt cold patch material according to claim 1, characterized in that: The base asphalt is 70# base asphalt; the unsaturated polyester resin is 3198 type resin or 196 type resin, the CAS number of 3198 type resin is 25037-66-5, and the CAS number of 196 type resin is 26098-37-3; the unsaturated monoacid is acrylic acid, oleic acid or linoleic acid; the curing agent is methyl ethyl ketone peroxide, cyclohexanone peroxide or acetylacetone peroxide; the accelerator is cobalt isooctanoate, cobalt cyclohexaneate or sodium dodecyl sulfonate; the dispersant is alkylene glycidyl ether, polypropylene glycol diglycidyl ether or o-tolyl glycidyl ether.
5. The method for preparing the reactive asphalt cold patch material as claimed in claim 1 comprises the following steps: (1) drying the aggregate at 105°C to constant weight and then cooling to room temperature for use; (2) weighing the aggregate, mineral powder, filler, diffusion oil and asphalt cold patch liquid respectively; (3) adding the weighed aggregate and filler into a mixer and stirring them thoroughly; (4) adding diffusion oil to the mixture obtained in step (3) and continuing to stir, adding asphalt cold patch liquid and stirring again after stirring, then adding mineral powder and continuing to stir until the mixture is formed; (5) putting the mixture obtained in step (4) into a sealed bag and avoiding direct sunlight.
6. The method for preparing the reactive asphalt cold patch material according to claim 5, characterized in that: In step (1), the aggregate is spread flat on a baking tray and placed in an oven at 105±5°C for drying. The aggregate is turned over and weighed every 1 hour. When the difference between the two weighings is less than 0.1%, it is considered to have reached a constant weight. The dried aggregate is then taken out, naturally cooled to room temperature (20±5°C) and kept dry for use to avoid moisture absorption or secondary contamination.
7. The method for preparing the reactive asphalt cold patch material according to claim 5, characterized in that: In step (3), the weighed aggregate and filler are added into the mixer together, and stirred at a low speed of 40-60 r / min for 30-60 s to initially disperse the aggregate and filler, and then stirred at a medium speed of 70-100 r / min for 60-90 s until the two are fully and evenly mixed.
8. The method for preparing the reactive asphalt cold patch material according to claim 5, characterized in that: In step (4), the diffusion oil is slowly added to the mixture obtained in step (3), and the mixture is stirred at a speed of 40-60 r / min for 30-60 s to fully disperse the diffusion oil in the mixture, and then the mixture is stirred at a speed of 70-100 r / min for 30-60 s; after the diffusion oil is evenly dispersed, the asphalt cold make-up liquid is added and stirred at a speed of 70-100 r / min for 60-90 s; then the mineral powder is added to the mixture, and the mixture is stirred at a speed of 70-100 r / min for 60-90 s until the mixture is formed.
Citation Information
Patent Citations
Safe and environment-friendly asphalt mixture for repairing pit slots in pavement in severe cold region and preparation method of safe and environment-friendly asphalt mixture
CN116496028A